Cerebral Syphilitic Gumma Mimicking Glioblastoma: A Case Report. Issue 1 (February 2016) - Wang, Tingzhong; Zhang, Liming; Zhao, Xianlin
Abstract : A case of suspected glioblastoma accompanied by systemic syphilis was referred to our institute for surgery. She was a 47-year-old woman presenting with headache and vomiting. A frontal mass with ring enhancement and surrounding edema was revealed by MRI. Although neurosyphilis was considered a differential diagnosis, surgery was performed and cerebral syphilitic gumma was confirmed by histology. To reduce misdiagnosis, we reviewed the related literature and summarized pathogenesis, radiologic features, and treatment strategy of cerebral syphilitic gumma.